The biomechanics and pathogenesis of seat belt syndrome: Literature review - E O Onuoha Clement; Onuoha Kelechukwu (Nigerian Journal of Medicine, 2019)
BACKGROUND: Seatbelts are the most effective means of providing occupant protection in a vehicular accident. This works by two mechanisms; by preventing ejection from the vehicle which has been reported to be the leading cause of both injury and death in accidents. Ejection converts the passenger into a “Passenger missile” and thrown out of the vehicle on impact against some stationary objects outside the vehicle – trees, earth, Pillars, culverts, and even on innocent by-standers! Also, ejected passengers can suffer roll-over injuries if the vehicle tumbles over and rolls over and/or crushes the ejected (1) passenger!(1) Seat belts prevent compression injuries, by deploying Airbags. In 70% of collisions, Seatbelts trigger off the deployment of air bags. These air bags restrain the occupant from being flung about in the vehicle and making contact with the vehicular panels like the steering wheel and other environmental surfaces in the vehicle - especially in frontal (or headon) collisions The airbags thus deployed prevent subsequent compression between the patient's organs and some of these framework thus preventing catastrophic compression/blunt injuries. Maximum protection is therefore achieved by the simultaneous use of seatbelts and airbags and this combination has been shown to reduce both the severity and fatality of motor vehicular injuries.(2) AIM: To do an extensive literature search looking for an explanation of how the seat belt, a seemingly safe/protective device can become a weapon of severe and at times very fatal injury.(3) METHODOLOGY: Literature search about “Mechanism of Seat-belt syndrome” was done via websites like “Netting the evidence” website:www.shef.ac.uk/scharr/ir/netting which gave us a comprehensive list of internet resources and also sites for virtual library. We also visited the Cochraine library via their website www.thecochrainelibrary.com which supplied us with the database of Abstracts and Reviews. We also looked at Systematic Review and Controlled trials of high impact collisions using robots, baboons and other mammals. We also used the Pubmed Advanced Search tool looking for the “Mechanism of Seat belt syndromes” RESULTS: The relative risk taken by an occupant without a seat-belt is 70% higher than that of a belted occupant. Therefore seatbelts, properly installed and properly worn, offers the best protection for the automotive occupant during impact. CONCLUSION: Seat-belts do not prevent accidents; they only work when accidents have occurred. The simultaneous action of seat-belts and air-bags have shown to reduce both the severity and fatality of motor vehicular injuries.